Early Goal-Directed Top-Down Influences in the Production of Speech - Strijkers, Kristof; Yum, Yen Na; Grainger, Jonathan; Holcomb, Phillip J. (Frontiers in Psychology, 2011)
It was recently reported that the conscious intention to produce speech affects the speed with which lexical information is retrieved upon presentation of an object (Strijkers, Holcomb & Costa, under review). The goal of the present study was to elaborate further on the role of these top-down influences in language production. In an ERP setting participants were required to overtly name pictures and words in one block of trials, while categorizing the same stimuli in another block of trials. The ERPs elicited by the naming task started to diverge very early on (~ 170 ms) from those elicited by the non-verbal semantic categorization task. Interestingly, these early ERP differences related to task intentionality were identical for pictures and words. From these results we conclude that (a) in line with Strijkers and colleagues (under review), goal-directed processes play a crucial role very early on in speech production, and (b) these task-driven top-down influences function at least in a domain-general manner by modulating those networks which are always relevant for the production of language, irrespective of which cortical pathways are triggered by the input.